2021
DOI: 10.1111/jac.12509
|View full text |Cite
|
Sign up to set email alerts
|

Do shoot anatomical characteristics allow rice to grow well under water deficit?

Abstract: Water deficit stress is considered to be one of the most important abiotic factors limiting plant growth and yield in many areas (Kramer & Boyer, 1997). Climate change as well as the decreasing fresh water availability for agriculture will increase the frequency and severity of water limitation to crop production (Madadgar et al., 2017). Rice (Oryza sativa L.), an essential crop for global food security, requires massive amounts of fresh water for irrigation. Various water-saving practices have been designed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…This fact indicated that an increase in R:S ratio triggered the ratio of N:P in shoots of upland rice. A higher R:S ratio indicated that more photosynthate was allocated to the roots to supply energy for the growth and development of upland rice roots under conditions of acid soil stress (Ouyang et al 2021). Therefore, organic carbon compounds released by roots into the soil were increased to be used by bacteria and AMF.…”
Section: Discussionmentioning
confidence: 99%
“…This fact indicated that an increase in R:S ratio triggered the ratio of N:P in shoots of upland rice. A higher R:S ratio indicated that more photosynthate was allocated to the roots to supply energy for the growth and development of upland rice roots under conditions of acid soil stress (Ouyang et al 2021). Therefore, organic carbon compounds released by roots into the soil were increased to be used by bacteria and AMF.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermis, cortex thickness, and number of vascular bundles were also significantly increased in the crosses compared to the parents. Most leaf anatomical structures are strongly impacted by water deprivation in plants [54]. Since leaves are the principal organs of internal water removal, drought-tolerant rice genotypes perform leaf anatomical modifications to conserve water.…”
Section: Discussionmentioning
confidence: 99%
“…Plant height, number of tillers and leaves, and the dry weight of the roots and shoots showed that the reduction of field capacity had a substantial impact on rice plant growth. Plants under drought stress have a reduced capacity to absorb water and nutrients, which inhibits photosynthesis and reduces plant growth, including plant height [11].…”
Section: Growth Charactersmentioning
confidence: 99%